PENGARUH LATIHAN SMALL SIDED GAMES TERHADAP PENINGKATAN AKURASI PASSING DALAM PERMAINAN SEPAKBOLA SSB PUTRA MAYANA KADUGEDE KUNINGAN - Bagas Saputra Bagas; Oman Hadiana; Dedi Iskandar (Journal of Physical Education and Sport Science, 2024)
Bagas Saputra (NIM : 182223025), with the title "INFLUENCE OF SMALL SIDED GAMES TRAINING TOWARDS INCREASING PASSING ACCURACY IN SSB PUTRA FOOTBALL GAMES MAYANA KADUGEDE KUNINGAN". Mayana Kadugede Kuningan. This research method uses an experiment with a One-Group Pretest-posttest research design with a population and a sample of 18 SSB Putra Mayana Kadugede players, with a sampling technique using saturated sampling so as to obtain a sample of 18 people, the research method using quantitative research methods, normality test This data uses the Shapiro Wilk test with significant values ​​for the pretest and posttest data of 0.521 and 0.039, which is greater than 0.05, so the data is normally distributed. Significant value for levene static 0.544 > 0.05, then normally distributed. Furthermore, the value of Tcount that can be obtained is -13,151 and for Ttable is 1.73961. Because the value of Tcount > Ttable, it can be concluded that there is an effect of small-sided games training on increasing passing accuracy.